Pengaruh Model Pembelajaran Kooperatif Tipe Teams Games Tournamet Terhadap Hasil Belajar Matematika Siswa Kelas 5 DI SD YPK 1 Hamadi - Nurul Mutmainnah; Zaidir Zaidir; Sri Wahyuni; Tri Kurniah Lestari; Winda Abriani (Mathematics Education Study Program, 2025)
This research aims to determine the effect of Teams Games Tournament type cooperative learning model on students' math learning outcomes at YPK 1 Hamadi Elementary School. This type of research is quantitative research with a quasi-experimental design. The sample selection technique used was random sampling. The sample in this study consisted of 2 groups, namely: the experimental group numbered 32 students, the control group numbered 32 students. This research was analyzed using SPSS 29 with normality test, homogeneity test, and hypothesis testing using t test. The results of hypothesis submission obtained the value of tcount> ttable which is 5.772> 0.1.669 thus Ha is accepted and Ho is rejected. So it can be concluded that there is a significant difference from learning using the Teams Games Tournament type cooperative learning model on student math learning outcomes at SD YPK 1 Hamadi. Keywords: Math, Learning, Outcomes,Teams Games Tournament.